Wees onzichtbaar - Isik, Murat (Amsterdam : Ambo|Anthos, 2018)
Een Turkse jongen groeit met zijn zusje op in de Bijlmer in de jaren 80 en 90.
Libris Literatuurprijs 2018
Nederlandse boekhandelsprijs 2018